ANTITUMOR AND ANTIOXIDANT POTENTIAL OF MAJORANA HORTENSIS EXTRACT BINDING TO THE SILVER NANOPARTICLES ON LUNGS CANCER CELL LINE - TAHER AL-ISAWI, Jameelah Kadhim; MOHAMMED, Aeshah Muhana; AL-HEETIMI, Dhafir T.A. (Studia Universitatis Babeș-Bolyai Chemia, 2023)
Majorana hortensis is widely distributed in the Mediterranean area with different medicinal potentials. In the current study, 1 mmol/L AgNO3 and 4% hydro-methanol leaf extract of M. hortensis at neutral pH (7.0) were successfully combined to create green Majorana hortensis – silver nanoparticles (MHE-AgNPs) after applying the reaction to sunlight for 30 minutes. MHE-AgNPs were characterized using atomic force microscope (AFM), high resolution-scanning electron microscope (HR-SEM) and energy-dispersive X-Ray (EDX). The size range of the MHE-AgNPs was between 50 and 95 nm, and they had a spherical form with smooth surface. With an IC50 of 36.39 µg/mL, MHE-AgNPs exhibited a 2,2′-diphenylpicrylhydrazyl (DPPH) scavenging ability in a concentration-dependent manner. The MTT colorimetric technique was used to determine the MHE-AgNPs cytotoxicity against A549 cell line. The green synthesis of MHE-AgNPs markedly improved the cytotoxic action of MHE-AgNPs against A549 cells. The multiparametric cytotoxicity assay using High-content Screening was employed. MHE-AgNPs was significantly reduced the cell viability, increased the membrane permeability, reduction in mitochondrial potential and stimulating the release of cytochrome c indicating the capability of MHE-AgNPs in killing A549 cells.